2021
DOI: 10.7773/cm.v17i3.818
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the age composition of catch of anchovy (Engraulis mordax) and alternatives for the management of the resource

Abstract: RESUMENSe analiza la estructura de la población de anchoveta antes de la perturbación causada por el fenómeno de "El Niño" durante 1982-1983. Se presentan los resultados del procesamiento de 20,205 datos de edad provenientes de muestreos biológicos de la captura comercial en Baja California durante el período [1978][1979][1980][1981][1982]. Se identifican las clases anuales responsables de las capturas de 1979-1981. Se establece que el grupo de un año de edad ha sido el principal generador de captura. Se descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…To date, the information gathered on age structure for anchovy species associated with highly productive systems has shown that some anchovies (e.g. genus Engraulis) appear to be relatively short-lived, with a maximum life span ranging from 4 to 5 years and a maximum asymptotic total length (L T ) ranging from 16 to 19 cm (Hayasi & Kondo, 1957;Mais, 1981;Vidal-Talamantes, 1991;Waldron, 1992;Basilone, et al, 2000). Recent studies using otolith microstructure analysis have reported fast growth patterns at the daily level for some anchovies and for other small pelagic fishes as well (La Mesa et al, 2009;Aldanondo et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…To date, the information gathered on age structure for anchovy species associated with highly productive systems has shown that some anchovies (e.g. genus Engraulis) appear to be relatively short-lived, with a maximum life span ranging from 4 to 5 years and a maximum asymptotic total length (L T ) ranging from 16 to 19 cm (Hayasi & Kondo, 1957;Mais, 1981;Vidal-Talamantes, 1991;Waldron, 1992;Basilone, et al, 2000). Recent studies using otolith microstructure analysis have reported fast growth patterns at the daily level for some anchovies and for other small pelagic fishes as well (La Mesa et al, 2009;Aldanondo et al, 2011).…”
Section: Introductionmentioning
confidence: 99%